Transitional Legal Protection through Physical Possession and Civil Remedies for Unregistered Girik Land in Indonesia: Perlindungan Hukum Transisional melalui Penguasaan Fisik dan Upaya Perdata terhadap Tanah Girik yang Belum Terdaftar di Indonesia - Octavia Alida Mochtar (Academia Open, 2026)
General Background Land remains a fundamental economic and social asset, and legal certainty in land administration is central to rights protection. Specific Background Girik is still widely used in Jakarta, Banten, and West Java as evidence of historical control over former customary land, yet its legal position has weakened after Government Regulation No. 18 of 2021 on land registration, with a recognition deadline of 2 February 2026. Knowledge Gap The available transitional legal safeguards and practical obstacles for girik holders whose parcels remain outside the national land administration system require clearer articulation. Aims This study examines the forms and mechanisms of legal protection for unregistered girik holders and identifies the main barriers they face. Results Using a normative juridical approach, the study finds that safeguards remain available through recognition of physical control, access to civil litigation provided no good-faith protected certificate exists, and the state obligation to systematically organize land registration; however, low public awareness, BPHTB cost burdens, limited historical documentation, and institutional capacity constraints hinder optimal legal certainty. Novelty The study consolidates a transitional protection framework that links physical possession recognition and civil remedies to the post-deadline evidentiary shift under PP 18/2021. Implications The study recommends accelerating PTSL, subsidizing registration fees, harmonizing BPHTB regulations, and digitizing legacy evidence to support an inclusive transition to formal land titles. Highlights: Historical tax-based documentation becomes limited to evidence of physical control after 2 February 2026. Civil claims remain available unless a good-faith certificate is legally protected. PTSL acceleration, fee subsidies, BPHTB harmonization, and legacy-evidence digitization are proposed to advance legal certainty. Keywords: Girik Land, Legal Protection, Legal Certainty